2016
DOI: 10.1017/s1355617716000412
|View full text |Cite
|
Sign up to set email alerts
|

Taking It at “Face Value”: The Use of Face Processing Strategies in Bipolar Disorder and Schizophrenia

Abstract: To our knowledge, this is the first study to explicitly examine and contrast face processing in BD and SZ. Our findings indicate a generalized impairment on face processing tasks in SZ, and the presence of a second-order configural face processing impairment in BD. It is possible that these face processing impairments represent a catalyst for the facial emotion recognition deficits that are commonly reported in the literature. (JINS, 2016, 22, 652-661).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…BD<SZ CPZe = chlorpromazine equivalents; PANSS = Positive and Negative Syndrome Scale. Note that this data has been presented in our previous report (Joshua et al, 2016) and is re-presented here to enable clarity for the reader.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…BD<SZ CPZe = chlorpromazine equivalents; PANSS = Positive and Negative Syndrome Scale. Note that this data has been presented in our previous report (Joshua et al, 2016) and is re-presented here to enable clarity for the reader.…”
Section: Discussionmentioning
confidence: 95%
“…This study should be considered in the context of the same limitations that beset our previous report, which includes an inability to control for medication effects due to the varied medications used in the current sample and an absence of the explicit assessment of manic symptom severity (see Joshua et al, 2016 for further details). Past research has also shown differences in emotion perception performance between BD patients with and without a psychosis history (Thaler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations